Determining Water Content and Distribution in PEMFCs to Predict Aging While in Storage. (24th August 2017) - Stariha, Sarah; Wilson, Mahlon S.; LaManna, Jacob M; Jacobson, David L; Hussey, Daniel S; Macauley, Natalie; Rau, Jon; Borup, Rod L.
Abstract : Proton membrane exchange fuel cells (PEMFCs) have the potential to be long term backup power sources with a startup time on the order of seconds. Water management is the key issue in being able to successfully store PEMFCs for extended periods of time. In this work custom made PEMFCs were humidified at various relative humidities (%RH) and subsequently stored for different lengths of time. The fuel cell's water content was then imaged at the National Institute of Standards and Technology (NIST) neutron imaging facility. The cells' startup performances were measured simulating quick startup conditions to define the effect of different water distributions.